Enhancing Supercapacitor Cell Capacitance through Liquid-Phase Exfoliation Synthesis of Graphene - Pratama, Buky Wahyu; Suhendar, Haris; Dwandaru, Wipsar Sunu Brams; Santoso, Iman (Journal of Multidisciplinary Applied Natural Science, 2025)
Our study investigates the remarkable capacitance performance of a supercapacitor cell featuring electrodes synthesized through the liquid-phase exfoliation (LPE) method using environmentally friendly linear alkylbenzene sulfonate (LAS) surfactant. We explored different synthesis temperatures (15, 30, and 90 °C) to evaluate their impact on reducing sonication time. The electrodes, created by drop-casting graphene onto a silver plate substrate and heated at 50 °C, demonstrated exceptional cyclic voltammetry (CV) and charging-discharging (CD) results. Notably, the graphene synthesized at 90 °C exhibited a maximum capacitance of 59 F/g at a 13 mV/s scan rate in a 1.3 M KOH electrolyte gel, leading to superior energy density as shown in the Ragone plot. Our findings highlight the crucial role of increased synthesis temperature in LPE, enhancing supercapacitor cells through the expansion of sp2-ordered grain size, evident in the Raman shift data's ID/IG increase.